Transient increase of serum Clara cell protein (CC16) after exposure to smoke. Issue 1 (January 1997) - Bernard, A; Hermans, C; Van Houte, G
Abstract : OBJECTIVES: Smoke inhalation is a well known cause of airways injury in firefighting personnel. The aim of this study was to evaluate whether toxic effects of smoke on the respiratory tract can be detected by measuring Clara cell protein (CC16), a recently described serum marker of lung function. METHODS: CC16 was measured by a sensitive latex immunoassay in the serum of six voluntary firefighters from a chemical plant who had inhaled smoke from the combustion of polypropylene for about 20 minutes. The protein was measured immediately after the fire and 10 days later. The values were compared with those of six control workers examined simultaneously. RESULTS: The mean (SD) concentration of CC16 in the serum of firefighters after the fire (54.4 (34.9) micrograms/l) was significantly higher than that of controls (19.5 (11.7), P = 0.04). 10 days later, serum CC16 from firefighters had returned to the concentrations found in controls (15.9 (2.76) v 17.7 (12.5)). With the values at day 10 as a baseline, the rise of serum CC16 was estimated at 328% on average (range 100%-564%). These changes were found in the absence of any functional sign of lung impairment. CONCLUSION: Acute exposure to smoke results in a transient increase of CC16 in serum due most likely to an increased permeability of the bronchoalveolar/blood barrier. Serum CC16 seems potentially to be a new biomarker for the early detection of acute airways injury caused by smoke.